Combined effects of cognitive impairment and pre-frailty on future frailty and death in older Mexican Americans. (3rd October 2019) - Downer, Brian; Al Snih, Soham; Howrey, Bret T.; Raji, Mukaila A.; Markides, Kyriakos S.; Ottenbacher, Kenneth J.
Abstract: Objectives: Impaired cognition and pre-frailty are associated with poor health outcomes. However, research has not examined the combined impact of cognitive impairment and pre-frailty on future frailty and mortality among older Mexican Americans. Methods: Data for this analysis came from the 2006–2007 and 2010–2011 waves of the Hispanic EPESE. The final sample included 639 Mexican Americans aged ≥77 years who were non-frail or pre-frail in 2006–2007. Frailty measure included weight loss, exhaustion, weakness, and slow walking speed. Participants were classified as non-frail (0 criteria) and pre-frail (1 criterion) at baseline. Cognitive impairment was defined as <21 points on the MMSE. At baseline, participants were grouped as: cognitively intact non-frail, cognitively intact pre-frail, cognitively impaired non-frail, and cognitively impaired pre-frail. Logistic and hazard regression models were used to evaluate the odds of being frail in 2010–2011 and risk for 10-year mortality. Results: Cognitively impaired pre-frail participants were more likely to become frail (OR = 4.82, 95% CI = 2.02–11.42) and deceased (HR = 1.99, 95% CI = 1.42–2.78). Cognitively impaired non-frail participants had significantly higher risk for mortality (HR = 1.55, 95% CI = 1.12–2.19) but not frailty (OR = 1.29, 95% CI = 0.50–3.11). Being cognitively intact and pre-frail at baseline was not significantly associated with being frail at follow-up (OR = 1.62, 95% CI = 0.83–3.19) or mortality (HR = 1.29, 95% CI = 0.97–1.71). Conclusions: Comorbid cognitive impairment and pre-frailty is associated with future frailty and mortality in older Mexican Americans. Screening for cognitive impairment may be effective for identifying pre-frail Mexican Americans who are at the highest risk of frailty and mortality.